State Medicaid Expansion and Citizens' Quality of Life*. (28th July 2017) - Flavin, Patrick
Abstract : Objectives: The U.S. Supreme Court's 2012 ruling on the Affordable Care Act was a federal exogenous shock that presented all states with the decision to continue their Medicaid program in its current form or expand it to include thousands of newly eligible recipients. This article takes advantage of this exogenous shock to evaluate the impact of Medicaid expansion on citizens' quality of life. Methods: I evaluate changes from 2010 to 2014 in low‐income citizens' subjective well‐being (SWB) using Gallup‐Healthways survey data and a difference‐in‐differences estimation strategy. Results: Average levels of SWB increased among low‐income citizens in states that expanded Medicaid eligibility compared to states that did not. In a series of placebo tests, I also demonstrate that the expansion had no effect on the SWB of middle‐ or high‐income citizens who are unlikely to directly benefit from more generous Medicaid eligibility requirements. Conclusions: The empirical findings suggest that the expansion of Medicaid has important implications for the well‐being of low‐income Americans and, more broadly, contribute to the growing literature on how government policy choices can concretely impact the quality of life that citizens experience.